Effects of drying on the bioactive compounds in organic sweet potatoes (Ipomoea batatas) - Pacheco, Okelyton Ayres; Silva, Luciana Alves da; Stafussa, Ana Paula; Bergamasco, Rita de Cassia; Scapim, Mônica Regina da Silva (Acta Scientiarum. Agronomy, 2026)
Sweet potato (Ipomoea batatas L.) is a source of vitamin A, carbohydrates, organic acids, and minerals. It is rich in bioactive compounds, making it a very healthy food. Indeed, it helps in the prevention of various diseases such as cardiovascular diseases, certain types of cancer, and in controlling the glycemic index of people with diabetes. Additionally, it provides nutrients for at-risk groups, such as children and pregnant women with deficiencies in magnesium and vitamin A. In its natural form, sweet potatoes have high water activity, making them highly perishable and reducing their shelf life. This study aimed to evaluate the influence of the drying process at different temperatures (50, 60, and 70°C) and thicknesses (1, 2, and 3 mm) on the antioxidant content and phenolic compounds of two sweet potato cultivars: BDI (Brasilândia) and BDII (not cataloged). The drying process was evaluated based on 10 mathematical models, comparing the coefficient of determination (R²), chi-square (χ²) value, and root mean squared error (RMSE). The Page model stood out for the BDI cultivar and the diffusion approximation and Page models were significant for the BDII cultivar. The total phenolic content ranged from 71.67 to 99.33 mg gallic acid equivalents 100 g-1. The 2,2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and ferric reducing antioxidant power (FRAP) methods were used to quantify antioxidant activity, with values ranging from 21.93 to 51.53 µmol Trolox 100 g-1 and 656.34 to 1021 µM ferrous sulfate 100 g-1, respectively. A drying temperature of 70°C combined with a thickness of 1 mm required a shorter drying time to reach the equilibrium moisture content, between 2 and 3 hours.